Investigation of the Morbidity and Mortality Patterns in Neonatal Intensive Care Units (NICUs) among Low Birth Weight (LBW) Neonates - Naidu, K. Dhanunjay; Rathod, Sachitra (Asian Journal of Clinical Pediatrics and Neonatology, 2022)
Background: The neonatal period is widely recognized as the most critical phase of human life in terms of susceptibility to morbidity and mortality. The assessment of neonatal outcome holds significant importance within the realm of obstetric and neonatal healthcare. In developing nations, the mortality rate of infants during the neonatal phase constitutes a significant proportion, ranging from 50% to 70%, of overall infant mortality. In India, the annual mortality rate for infants is estimated to be one million. Aim: Investigation of the morbidity and mortality patterns in neonatal intensive care units (NICUs) among low birth weight (LBW) neonates. Materials and Methods: The present study involved a comprehensive analysis of data pertaining to the incidence of preterm deliveries, diverse morbidity indicators, mortality trends, and the therapeutic interventions administered within the Neonatal Intensive Care Unit (NICU). The study gathered pertinent information, such as maternal characteristics (age, address, socioeconomic status, educational level), maternal weight, and various risk factors. Additionally, data on the order of birth, gestational age, antenatal steroid use, premature rupture of membranes, and mode of delivery were also collected. Results: Among a total of 800 infants, 220 were born with low birth weight (LBW). Of these LBW infants, 120 (54.55%) were born prematurely, while 100 (45.45%) were classified as having intrauterine growth restriction (IUGR) at term. The prevalence of low birth weight (LBW) infants in the present study was found to be 27.5%. The prevalent morbidities observed in low birth weight (LBW) infants were neonatal hyperbilirubinemia, accounting for 45.45% of cases, followed by early-onset sepsis (EOS) at 30.91%, birth asphyxia at 20.45%, respiratory distress at 13.64%, late-onset sepsis (LOS) at 8.18%, and meconium aspiration syndrome (MAS) at 6.82%. The primary factor contributing to early neonatal mortality in preterm low birth weight infants was birth asphyxia, accounting for 47.06% of cases. This was followed by hyaline membrane disease, which accounted for 22.73% of cases, and sepsis, which accounted for 11.76% of cases. Conclusion: The findings of this study indicate that preterm infants accounted for 54.55% of the cases of low birth weight infants. The relationship between morbidity and mortality in low birth weight (LBW) infants exhibited an inverse correlation with both birth weight and gestational age.